Eis que a língua se fez nova: você, vocês, a gente e os rearranjos gramaticais em três versões da Bíblia - Silva, Luciano Kennedy Vieira e (2023)
Innovative pronouns' study shows that pronoun forms implemented as você, vocês and a gente has caused grammatical rearrangements in Brazilian Portuguese, such as the third person possessive pronouns use to represent the second one, variations in imperative mood and the so-called ―address mixture‖. Manuals and traditional grammar, in turn, still do not consider in their pronominal chart the use of those innovative forms, consequently, they do not introduce its resulting reorganizations. Based on the Theory of Language Variation and Change, this research has the general objective of analyze and describe grammatical reorganizations in three Brazilian Portuguese biblical editions: A Bíblia Viva (Living Bible), Nova Tradução na Linguagem de Hoje (Today‘s English Version) and Nova Almeida Atualizada (similar to the English Standard Version). These Bible versions use você, vocês and a gente in their texts, conditioning grammatical rearrangements occurrence in their redaction. Because it is a sacred book for Christianity, in its many aspects, the Bible could be considered a social prestige publication and be classified as a sensitive text. Furthermore, texts considered sacred, in theory, would be more resistant to variation and change. Guided by Weinreich, Labov and Herzog (2006), Labov (2006, 2008 [1972]), Lopes (2004, 2007, 2008 and 2012), Scherre (2007), Faraco (2007, 2008 and 2017), and Faraco and Zilles (2017), this study seeks to fulfill its general objective through the following specific objectives: (I) To examine the alternation degree tu / você, nós / vocês and nós / a gente in the biblical text. (II) To investigate possible reorganizations in the possessive pronouns context. (III) To inquire changes in the imperative mood form of representation. (IV) To verify the ―mixture of treatment‖ occurrence in the analyzed texts. In order to achieve these objectives, from the three biblical versions studied were selected for analysis, the Pentateuch, formed by the Old Testament's five first books (Genesis, Exodus, Leviticus, Numbers and Deuteronomy) and the Gospels formed by the New Testament's four first books (Matthew, Mark, Luke and John). The data collected show high percentage levels of você and vocês variants, with low recurrence of the variant a gente. The numbers point to the obsolescence use of vós as well. Given the above, were also found in the sample, grammatical rearrangements regarding possessive pronouns use, representing the imperative mood, as well as the ―mixtures of treatment‖ occurrence.